ANALISIS PERAN IPAS MEWUJUDKAN PROFIL PELAJAR PANCASILA SEBAGAI GAMBARAN IDEAL PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR - Benu, Asti Yunita; Mbuik, Heryon Bernad (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2024)
Abstract. The aim of this research is to analyze and describe the role of IPAS in realizing the Pancasila Student Profile as an ideal description of character formation for elementary school students at GMIT Kuanino 1 Elementary School, Kupang City. This type of qualitative research uses descriptive analysis methods carried out by means of observation and interviews. The research results found that the main role of science and science subjects is as a means of introducing Pancasila values ​​to students. Through science learning, students are invited to understand the meaning and importance of the noble values ​​of Pancasila such as mutual cooperation, justice, democracy, unity and oneness. Students at GMIT Kuanino 1 Elementary School, Kupang City, consisting of various ethnicities and religions, are taught by teachers to uphold an awareness of mutual tolerance. This is a real implementation of the IPAS material. Apart from maintaining the living environment around the school, students are taught to maintain good social relations between each other in the school environment. Abstrak. Tujuan penelitian ini yaitu untuk menganalisis dan mendeskripsikan Peran IPAS dalam mewujudkan Profil Pelajar Pancasila sebagai gambaran ideal Pembentukan Karakter Siswa Sekolah Dasar pada SD GMIT Kuanino 1 Kota Kupang. Jenis penelitian kualitatif dengan mengunakan metode deskripsi analisis yang dilakukan dengan cara observasi dan wawancara. Hasil penelitian ditemukan bahwa peran utama mata pelajaran IPAS adalah sebagai sarana untuk mengenalkan nilai-nilai Pancasila kepada para siswa. Melalui pembelajaran IPAS, siswa diajak untuk memahami makna dan pentingnya nilai-nilai luhur Pancasila seperti gotong royong, keadilan, demokrasi, persatuan, dan kesatuan. Siswa di SD GMIT Kuanino 1 Kota Kupang terdiri dari beragam suku dan agama diajarkan guru untuk menjunjung kesadaran toleransi Bersama. Hal ini merupakan implementasi nyata dari materi IPAS. Selain memelihara lingkungan hidup sekitar sekolah, siswa diajarkan memelihara perilaku hubungan sosial yang baik antara sesame di lingkungan sekolah.